COMPARATIVE IN VITRO ANTIFUNGAL ACTIVITY OF SINGLE AND COMBINED EXTRACTS OF MICHELIA ALBA AND IMPATIENS BALSAMINA AGAINST CANDIDA ALBICANS - Wiranata Nyoman; Marta Setiabudy; Ni Wayan Widhidewi (Meditory : The Journal of Medical Laboratory, 2026)
Background: Infections caused by Candida albicans are increasingly prevalent, particularly among immunocompromised individuals, and are further complicated by rising resistance to synthetic antifungal agents such as azoles. This has led to growing interest in traditional medicinal plants as alternative antifungal sources. Objective: This study aimed to evaluate the in vitro antifungal activity of single and combined extracts of Michelia alba and Impatiens balsamina against Candida albicans. Methods: Both plant extracts were obtained by ethanol maceration and phytochemically screened. Antifungal activity was evaluated using the disk diffusion method with 20 µL (20 mg/disc) of crude extract. Extract combinations (1:3, 1:1, and 3:1) were tested in triplicate, and data were analyzed using the Kruskal–Wallis and Mann–Whitney tests. Results: Impatiens balsamina extract showed the largest inhibition zone (10.72 mm), followed by the 3:1 combination (9.91 mm) and Michelia alba extract (7.83 mm). All extracts exhibited moderate antifungal activity, with significant differences among groups (p = 0.009). Conclusions: Both plant extracts, individually and in combination, demonstrated antifungal activity against Candida albicans, suggesting their potential as candidates for natural antifungal agents.